1972
DOI: 10.1021/jm00274a003
|View full text |Cite
|
Sign up to set email alerts
|

Centrally acting emetics. 6. Derivatives of .beta.-naphthylamine and 2-indanamine

Abstract: Cannon, et al.10% NaOH. The aq so In was washed twice with Et20 and was then neutralized with glacial HOAc. The soln was saturated with solid NaHCOg, and the product was extd with several portions of C6H6. Evapn of the dried solvent left 17.7 g (55.5% crude yield) of product of mp 88-95°. Recrystn from 100 ml of z-PrOAc gave 13.5 g (42.3% yield) of crystals, mp 88-90°.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

1972
1972
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(24 citation statements)
references
References 3 publications
0
24
0
Order By: Relevance
“…Previously, the addition of N-dialkyl groups to restricted analogs of dopamine has been shown to increase their potency on behavioral test for dopamine agonist activity (29)(30)(31)(32). Therefore, it was not surprising that the addition of N-dimethyl groups to the geometric isomers of 2-amino-1-(3,4-dihydroxyphenyl)cyclobutane increased their affinity for the [3H]dopamine binding site.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, the addition of N-dialkyl groups to restricted analogs of dopamine has been shown to increase their potency on behavioral test for dopamine agonist activity (29)(30)(31)(32). Therefore, it was not surprising that the addition of N-dimethyl groups to the geometric isomers of 2-amino-1-(3,4-dihydroxyphenyl)cyclobutane increased their affinity for the [3H]dopamine binding site.…”
Section: Discussionmentioning
confidence: 99%
“…1). Previous studies with certain derivatives of A-5,6-DTN indicated that they exert dopamine-like activity in the central nervous system, because they are potent emetic agents and produce gnawing behavior in mice (8,9). Some of these analogs have also been shown to produce typical (32-adrenergic actions (10).…”
Section: Dopamine Can Cause Vasodilation By Several Mechanisms (1)mentioning
confidence: 99%
“…[1][2][3] It serves as the starting material for the preparation of several drugs such as the 2-aminotetralins, [4][5][6][7][8] which act as dopaminergic agonists in the treatment of Parkinson's disease. 9 It is also used as the key intermediate in the synthesis of many other naphthalene derivatives. 10, 11 2,6-Dihydroxynaphthalene (1) has been prepared by two general methods.…”
Section: 6-dihydroxynaphthalenementioning
confidence: 99%